Cook with me : 150 recipes for the home cook - Guarnaschelli, Alex, 1969- (Clarkson Potter/Publishers, 2020)
The Chopped judge and Iron Chef shares 150 family recipes, including selections prepared throughout her life by her cookbook-editor mother, Maria Guarnaschelli, including Blueberry Crumble, Baked Ziti and Godfather- and Goodfellas-style spaghetti and meatballs.